Improved Source Location And Evaluation Of Seismic Events Over A Deep Coal Mine - D. S. Choi (International Conference on Ground Control in Mining, 1990)
This paper describes an improved source location technique for microseismic events related to coal mining. A system of non- linear distance equations is solved with the use of the Newton-Raphson method. This computational method is- advantageous when the number of geophones is limited. In addition, this paper includes the results of the analysis of data from several instruments which characterize both mine seismicity and environmental noise such as vehicle traffic. Analysis of the mine seismicity has contributed to a better understanding of caving above a longwall gob and of what constitutes stable ground conditions.